Мониторинг стабильности технологического процесса изготовления электроизоляционных систем тяговых электрических машин - Беспрозванных, А.В.; Рогинский, А.В. (Електротехніка і електромеханіка, 2017)
Показано, что сопротивление изоляции может служить информативным параметром стабильности технологического процесса изготовления электроизоляционных систем тяговых электрических машин. Установлено, что сопротивление изоляции находится в пределах ±3σ относительно среднего значения каждой выборки трех вариантов исполнения электроизоляционной системы. Представлены контрольные карты индивидуальных значений и кумулятивных сумм сопротивления изоляции магнитной системы тяговых электродвигателей постоянного тока. Показано, що опір ізоляції можливо застосовувати в якості інформативного параметру стабільності технологічного
процесу виготовлення електроізоляційних систем тягових електричних машин. Встановлено, що опір ізоляції знаходиться в межах ±3σ відносно середнього значення кожної вибірки трьох варіантів виконання електроізоляційної системи. Представлено контрольні карти індивідуальних значень та кумулятивних сум опору ізоляції магнітної системи тягових електродвигунів постійного струму Introduction. Electrical insulation systems make up about 0.03
% of the traction electric machines (TEM) mass, but they are of
exceptional importance and affect the design capabilities and
manufacturing techniques of electric machines, ultimately - on
their specific weight and overall dimensions, on the reliability
and durability of the TEM. Purpose. The monitoring of the stability of the manufacturing process of electrical insulating systems of the TEM based on the insulation resistance measurements. Methodology. The analysis of the manufacturing process
is carried out for three versions of the case of insulation of the
magnetic system of the DC traction electric motor. Practical
value. Construction and analysis of special graphs (charts) of
individual values and cumulative sums of insulation resistance,
sliding range MR allow to find out whether the technological
process of manufacturing electric insulating systems of traction
electric machines is in a statistically controllable state